PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN MEMECAHKAN MASALAH DAN BERPIKIR KRITIS SISWA DI SMP YAYASAN PERGURUAN KELUARGA PEMATANGSIANTAR 2021/2022 - Tridelpina Purba, Sumarny; Perayanti Sinaga, Dian; Nurazizah, Melani (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study aims to determine the effect of the Project-Based Learning model on students' problem solving and critical thinking skills. The population in this study were eighth-grade students of Yayasan Perguruan Keluarga Private Junior High School, Pematangsiantar, in the 2021/2022 academic year. The sample consisted of four classes totaling 118 students. Cluster random sampling was used to select class VIII-3 (30 students) as the control class and VIII-1 (30 students) as the experimental class. The instrument used in this study was a test. The data were analyzed to determine the mean, median, mode, standard deviation, linearity test, normality test, homogeneity test, regression test, t-test, and f-test. Data analysis using ANOVA with a significance level of 5% (α = 0.05) using SPSS 21 software revealed an effect of Project-Based Learning on problem-solving skills. The calculated F-value was greater than the F-table (8.184 > 4.004) and the significance value was less than 0.05 (0.000 < 0.05). The hypothesis testing on students' critical thinking skills showed an F-value greater than the F-table (19.208 > 4.004) and the significance value was less than 0.05 (0.000 < 0.05). Therefore, Ha was accepted and H0 was rejected. This indicates that the Project-Based Learning (PjBL) model has an effect on students' problem-solving and critical thinking skills on the human excretory system topic in eighth-grade students at Yayasan Perguruan Keluarga Pematangsiantar Private Junior High School in the 2021/2022 academic year.